“Scale” as Cultural Attribution: Anthropological Contributions in Political Ecology Studies - Pangeran P. P. A. Nasution (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
The environment is as place where people live while providing various possibilities to meet their needs. Humans are connected to nature through culture by a system of symbols, meanings, and values. The problematic relation between humans and the environment currently known as “hybrid complexity” involves another analytical tradition such as political economy, symbolic anthropology, and historical anthropology. Political ecology as a study with a transdisciplinary perspective try to gain an explanation about the relationship between humans and the environment not in a static and harmonious fabricate, but in chaotic (noisy and complicated) interconnections. The basic assumption of the study of political ecology is the issue of inequality: the existence of asymmetric forces that produce socio-economic inequality, and these problems are present in the relation between human life and the environment. Humans relate to the environment through a diverse network of interests at various levels and multi-capacities. The scale is one of the important concepts that deserve scrutiny in order to understand the workings of the political ecology approach. The scale is the “heuristic terminology” of culture. Humans are the main element of the scale that connects culture to its reality and as a feature of culture itself. Thus, the scale can be understood as a cultural attribution of the unit of explanation which includes the size, level, and relations of events and actions that mediate human relations and the environment of natural phenomena and socio-cultural phenomena.